All the broken people : a novel - Konen, Leah (G. P. Putnam's Sons, 2020)
"Fleeing Brooklyn with little more than a suitcase and her trusty dog, Lucy King heads to rustic Woodstock , New York, eager to lose herself in a quiet life where her past can never find her. But when she meets Vera and John, the alluring couple next door, their friendship proves impossible to resist. Just as Lucy starts to think the worst is behind her, the couple delivers a staggering bombshell: they, too, need to escape their troubles--and the only way they can begin their new life is if Lucy helps them fake John's death. Afraid to lose her newfound support system, Lucy reluctantly conspires with them to stage an "accidental" death on a hike nearby. It's just one little lie to the police, after all, and she knows a thing or two about the importance of fresh starts. But what begins as an elaborate ruse turns all too real when John turns up dead in the woods the morning after their hike. Now, Lucy must figure out who she can trust and who's pulling the strings of her tenuous new life . . . before she takes the fall for murder."--